Improving Nonspecific Binding and Solubility: Bicycloalkyl Groups and Cubanes as para‐Phenyl Bioisosteres. (27th March 2017) - Auberson, Yves P.; Brocklehurst, Cara; Furegati, Markus; Fessard, Thomas C.; Koch, Guido; Decker, Andrea; La Vecchia, Luigi; Briard, Emmanuelle
Abstract: Bicycloalkyl groups have been previously described as phenyl group bioisosteres. This article describes the synthesis of new building blocks allowing their introduction into complex molecules, and explores their use as a means to modify the physicochemical properties of drug candidates and improve the quality of imaging agents. In particular, the replacement of an aromatic ring with a bicyclo[1.1.1]pentane‐1, 3‐diyl (BCP) group improves aqueous solubility by at least 50‐fold, and markedly decreases nonspecific binding (NSB) as measured by CHI(IAM), the chromatographic hydrophobicity index on immobilized artificial membranes. Structural variations with the bicyclo[2.2.2]octane‐1, 4‐diyl group led to more lipophilic molecules and did not show the same benefits regarding NSB or solubility, whereas substitutions with cubane‐1, 4‐diyl showed improvements for both parameters. These results confirm the potential advantages of both BCP and cubane motifs as bioisosteric replacements for optimizing para ‐phenyl‐substituted molecules. Abstract : Lifting the fog : Many drug and tracer candidates contain para ‐substituted phenyl groups, and we show that their physicochemical properties can be improved by bioisosteric substitutions. While bicyclo[2.2.2]octyl has properties similar to those of para ‐phenyl, the use of bicyclo[1.1.1.]pentyl and cubane‐1, 4‐diyl leads to strongly increased water solubility, and to a marked decrease in nonspecific binding (NSB). This is particularly important for PET imaging tracers, as the lower the NSB signal, the less "foggy" images will be.